A game engine to make games as multi-agent systems. (February 2020) - Marín-Lora, Carlos; Chover, Miguel; Sotoca, José M.; García, Luis A.
Highlights: A game engine to create games as multi-agent systems. The engine definition leans on a formal specification of a multi-agent system. The behaviour specification system is based on first-order logic. Game mechanics can be defined by just five conditions and four actions. A set of use cases are presented along with their game mechanics. Abstract: Video games are applications that present design patterns that resemble multi-agent systems. Game objects or actors are like autonomous agents that interact with each other to describe complex systems. The purpose of this work is to develop a game engine to build games as multi-agent systems. The actors or game engine agents have a set of properties and behaviour rules with the end to interact with the environment of the game. The behaviour definition is established through a formal semantic based on predicate logic. The proposed engine tries to fulfil the basic requirements of the multi-agent systems, by adjusting the characteristics of the system, without affecting its potential. Finally, a set of games are introduced to validate the operation and possibilities of the engine.